Fluorophobic Effect Promoting Lamellar Self‐Assembly of Donor Acceptor Dyes. Issue 20 (8th August 2018) - Haenle, Johannes Christian; Stöckl, Yannick; Forschner, Robert; Haenle, Elena; Laschat, Sabine
Abstract: To combine liquid crystalline and linear optical properties in the same molecule, the fluorophobic effect was probed for the first time in donor acceptor dyes. Thus, a series of mono‐, bi‐, and tricyclic donor acceptor dyes with 1 H, 1 H ‐perfluorinated alkyl chains of different lengths as donor units and nitrile, malononitrile or barbiturate as acceptor units was synthesized in 5 steps and 1.4–6.6 % overall yield. UV/Vis and fluorescence spectroscopy, cyclic voltammetry and DFT calculations revealed that absorption and emission maxima, Stokes shifts and LUMO energies were mainly governed by the chromophore size and acceptor strengths. The perfluorinated chain was electronically almost decoupled from the remaining chromophore and induced only slight changes of the absorption maxima as compared to the alkyl substituted counterparts. However, in contrast to the non‐mesomorphic alkyl donor‐substituted derivatives, the perfluorinated donors resulted in self‐assembly into partially interdigitated SmA bilayers according to differential scanning calorimetry (DSC), polarizing optical microscopy (POM), X‐ray diffraction (WAXS, SAXS) studies and electron density profile calculations. Abstract : The lamellar self‐assembly of novel rigidified donor‐acceptor dyes is strongly promoted by the fluorophobic effect without comprising the absorption and emission of the dyes. The linear optical properties are controlled by the chromophore size and the strength of the acceptor unit.